Economic nationalism and the home court advantage - Choudhury, Arnab; Jandhyala, Srividya; Nandkumar, Anand (Strategic Management Journal, 2025)
Abstract Research Summary Political and regulatory actors routinely adopt or enforce policies to protect domestic firms at the expense of foreign firms. However, since courts are expected to be neutral and act independently, a question arises whether (and why) they discriminate against foreign firms. We argue that the courts are nationalistic, which emanates from judges differentiating between in‐group (domestic) and out‐group (foreign) members. In a sample of 58,754 patent disputes adjudicated by US federal district courts between 1983 and 2016, we find domestic patent holders and challengers are more successful than their foreign counterparts. Rulings involving foreign firms are more likely to exhibit nationalistic rhetoric. Judicial ideology moderates the differential odds of success between domestic and foreign firms. Thus, the legal system is another source of economic nationalism. Managerial Summary Multinational firms might face a disadvantage relative to domestic firms because politicians and regulators are nationalistic; they routinely adopt policies that favor domestic firms. If courts are neutral, this disadvantage should not exist in litigation between multinational and domestic firms. On the contrary, if courts are also nationalistic, domestic firms should enjoy an advantage and greater success than multinational firms in judicial verdicts. Using data on patent disputes in the United States observed over a 33‐year period, we find domestic patent holders and challengers are more successful than their foreign counterparts suggesting that the legal system is another source of economic nationalism. Rulings involving multinationals are more likely to exhibit nationalistic rhetoric. Judicial ideology moderates the differential odds of success between domestic and multinational firms.